2023
DOI: 10.7759/cureus.40980
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Cefepime-Induced Neurotoxicity: A Systematic Review

Abstract: There has been increased use of cefepime due to concerns about the nephrotoxic effects of the combined use of vancomycin and Zosyn. However, cefepime is associated with neurotoxicity. We conducted a systematic review using online data to explore the trend of cefepime-induced neurotoxicity over the last 10 years. Forty-six articles met our inclusion criteria, including 73 cases of cefepime-induced neurotoxicity. We noticed a steady increase in the reports of cefepime-induced neurotoxicity, from one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…In a systematic review conducted by Ajibola et al, it was observed that patients aged 65 and older accounted for more than 50% of the cases, suggesting a strong association between neurotoxicity caused by cefepime and older age; however, CIN can even affect pediatrics. 15 , 16 In a retrospective study by Appa et al, which included 198 patients, it was noted that a decreased level of consciousness was the most prevalent clinical feature, affecting 80% of the patients. This was followed by disorientation, which was observed in 47% of cases, and myoclonus which was observed in 40%.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review conducted by Ajibola et al, it was observed that patients aged 65 and older accounted for more than 50% of the cases, suggesting a strong association between neurotoxicity caused by cefepime and older age; however, CIN can even affect pediatrics. 15 , 16 In a retrospective study by Appa et al, which included 198 patients, it was noted that a decreased level of consciousness was the most prevalent clinical feature, affecting 80% of the patients. This was followed by disorientation, which was observed in 47% of cases, and myoclonus which was observed in 40%.…”
Section: Discussionmentioning
confidence: 99%